Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 10224 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Ailanthus altissima (Mill.) Swingle", "HasCoordinate is true", { "or" : [ "BasisOfRecord is Human Observation", "BasisOfRecord is Specimen", "BasisOfRecord is Living Specimen" ] } ] } The dataset includes 10224 records from 149 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001668-150912100344238/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences